2017
DOI: 10.1016/j.apcatb.2016.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodechlorination of trichloroethylene over Pd supported on swellable organically-modified silica (SOMS)

Abstract: The catalytic activity and resistance to poisoning of Pd catalysts supported on swellable organically-modified silica (SOMS) were investigated for hydrodechlorination (HDC) of trichloroethylene (TCE). The promising catalytic activity of 1% Pd/SOMS sample was attributed to the high affinity of SOMS for organics and its high hydrophobicity. While latter characteristic repels water, the adsorptive capacity for organics allows TCE dissolved in aqueous media to concentrate inside the pores, in the vicinity of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Hence, the properties of Ir/SBA‐3 and Ir/AlSBA‐3 in removal of TCE from water could be strongly related with the hydrophobicity of these materials. Additionally, the hydrophobic nature of Ir/AlSBA‐3 and Ir/SBA‐3 acts as a benign protection layer to restrict both the agglomeration or redispersion or leaching effect, as it was confirmed by TEM analysis for spent catalysts (Figure ) …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Hence, the properties of Ir/SBA‐3 and Ir/AlSBA‐3 in removal of TCE from water could be strongly related with the hydrophobicity of these materials. Additionally, the hydrophobic nature of Ir/AlSBA‐3 and Ir/SBA‐3 acts as a benign protection layer to restrict both the agglomeration or redispersion or leaching effect, as it was confirmed by TEM analysis for spent catalysts (Figure ) …”
Section: Resultsmentioning
confidence: 72%
“…The activity can be also influenced by hydrophobicity of the catalysts. Based on the literature data hydrophobicity plays beneficial role in protection of active phase from poisoning and leaching and helps the kinetics. Hence, the properties of Ir/SBA‐3 and Ir/AlSBA‐3 in removal of TCE from water could be strongly related with the hydrophobicity of these materials.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have reported on a new class of materials, swellable organically-modified silica (SOMS), as catalyst support for Pd used in HDC of TCE. 49 SOMS is an extremely hydrophobic and adsorptive material, which can adsorb various types of organic compounds from air and water. When sufficient adsorption takes place, pore filling can initiate the physical expansion of the SOMS volume, called as "swelling".…”
Section: Introductionmentioning
confidence: 99%
“…The higher catalytic activity over Pd/SOMS was attributed to the swelling behavior of SOMS, which only adsorbed TCE molecules from the solution (hydrophobicity) and concentrated them in the vicinity of the Pd active sites inside the pores. 49 Additionally, the Pd active sites were protected by the strong hydrophobicity of SOMS from poisoning by sulfur anions dissolved in water. 49 It was observed that the Li 2 S poisoned-1% Pd/SOMS maintained its catalytic activity compared to fresh 1% Pd/SOMS whereas Li 2 S poisoned-1% Pd/Al 2 O 3 catalyst was completely deactivated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation